2017
DOI: 10.3390/su9112112
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Reporting and Firm Value: Evidence from Singapore-Listed Companies

Abstract: Abstract:As sustainability reporting has emerged as one of the most critical issues in the business world, this research aims to investigate the relationship between sustainability reporting and firm value based on listed companies in Singapore. We use an established sustainability reporting assessment framework and test how both the adoption and quality of sustainability reporting are related to a firm's market value. Empirical results suggest that sustainability reporting is positively related to firm's mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
116
1
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(184 citation statements)
references
References 39 publications
13
116
1
17
Order By: Relevance
“…In relation to stock prices, Ansari [13] found that sustainability reporting had a positive effect on stock prices of real estate companies. Findings of other studies such as Loh et al [14] and Lourenc¸o et al [15] have shown the usefulness of sustainability reporting. However, previous research findings also show that there are weaknesses in sustainability reporting, such that sustainability reporting is more helpful for internal communication than for external communications [10,16] and that sustainability reporting provides information on the financial value more qualitatively than quantitatively [17].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In relation to stock prices, Ansari [13] found that sustainability reporting had a positive effect on stock prices of real estate companies. Findings of other studies such as Loh et al [14] and Lourenc¸o et al [15] have shown the usefulness of sustainability reporting. However, previous research findings also show that there are weaknesses in sustainability reporting, such that sustainability reporting is more helpful for internal communication than for external communications [10,16] and that sustainability reporting provides information on the financial value more qualitatively than quantitatively [17].…”
Section: Introductionmentioning
confidence: 75%
“…Increasing the quality of sustainability disclosure over time does not indicate an improvement in financial performance. On the other hand, Loh et al [14] examined and found that firms with sustainability reporting have higher firm values than firms that do not present sustainability reporting. In addition, the quality of sustainability reporting also has an impact on firm value.…”
Section: Value Relevance Of Financial Statementsmentioning
confidence: 99%
“…Accounting and finance researchers have also documented important findings on the benefits of CSR, such as reduced business risk, information asymmetry, cost of capital, insider trading profit and analyst forecast errors and increased customer trust and loyalty, employee retention, productivity, and company reputation. Yet, prior studies do not show a consistent relationship between CSR and firm value, that is, positive [9,10], neutral [11] and negative [12] relationships were all documented.…”
Section: Introductionmentioning
confidence: 84%
“…The supporters of positive relationship are the authors of [9,10], who find a positive relationship between CSR disclosure, measured by voluntary carbon emission disclosure, and stock return. There were positive relationships found between CSR performance and firms' bond price or yield spread [17] and stock return [18].…”
Section: Csr and Value Relevance Of Financial Reportingmentioning
confidence: 99%
“…As a result, a model of assessing the impact of sustainability performance (SP) on financial performance (FP) was proposed, such a model allows us to assess the financial value of the stability of a company's development [11]. Peculiarities of corporate reporting with the goal of creating a positive image of the company, the advantages of financial and non-financial reporting from the point of view of planning sales volumes are presented in the works of a group of Singaporean scientists [12].…”
Section: Literature Reviewmentioning
confidence: 99%